THE PROBLEM OF THE ESSENTIAL „MARKER’S” ATTACHED TO DETERMINATOIN OF THE LEVEL’S OF THE POLITICAL STABILITY/UNSTABILITY - Власенко, Д.Й. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article is devoted to the problems of defining criterions of the levels political stability/unstability of the society. Well-founded conclusion, that the main difficulty is the searching of such criterions there is the mutually exclusive property. The basis of the stability of the one thing political institutions is unstability of the another thing political institutions and the wrong way. Propose the conclusion that the level’s stability of the society depended of the people activity which supporting of the some political institutions and processes.